2008
DOI: 10.1086/587775
|View full text |Cite
|
Sign up to set email alerts
|

The Magnetohydrodynamics of Shock‐Cloud Interaction in Three Dimensions

Abstract: The magnetohydrodynamic evolution of a dense spherical cloud as it interacts with a strong planar shock is studied, as a model for shock interactions with density inhomogeneities in the interstellar medium. The cloud is assumed to be small enough that radiative cooling, thermal conduction, and self-gravity can be ignored. A variety of initial orientations (including parallel, perpendicular, and oblique to the incident shock normal) and strengths for the magnetic field are investigated. During the early stages … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
107
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(117 citation statements)
references
References 33 publications
6
107
4
Order By: Relevance
“…Rather than using a discrete cloud boundary, we use the same type of smooth cloud density and temperature profiles as, among others, Nakamura et al (2006) and Shin et al (2008). This means assuming pressure equilibrium and a density profile of the form…”
Section: Initial Shock-cloud Modelmentioning
confidence: 99%
“…Rather than using a discrete cloud boundary, we use the same type of smooth cloud density and temperature profiles as, among others, Nakamura et al (2006) and Shin et al (2008). This means assuming pressure equilibrium and a density profile of the form…”
Section: Initial Shock-cloud Modelmentioning
confidence: 99%
“…However, because a large grid was required for their cloud they were unable to run a 'high' resolution simulation to test this. One of the few 3D MHD resolution tests in the literature was performed by Shin et al (2008) for a spherical cloud using a non-AMR code at resolutions of R 120 and R 60 and concluded that most aspects of the MHD shock-cloud interaction were well converged at both resolutions. To our knowledge, the only resolution tests for a 3D purely hydrodynamic shock-filament interaction were performed by Pittard & Goldsmith (2016), who demonstrated that convergence was possible at a resolution of R 32 .…”
Section: Convergence Studiesmentioning
confidence: 99%
“…Other studies have reported on the effects of additional processes on the interaction, such as magnetic fields (e.g. Mac Low et al 1994;Shin-S., Stone & Snyder 2008), radiative cooling (e.g. Mellema, Kurk & Röttgering 2002;Fragile et al 2004;Yirak, Frank & Cunningham 2010) and thermal conduction (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the lateral magnetic pressure can effectively prevent clump penetration into the jet. Moreover, assuming that clumps managed to enter the jet, magnetic pressure could suppress the development of shocks, induce magnetic dissipation and non-thermal activity, and strongly change the clump disruption process, softening or potentiating it (e.g., Jones et al 1996;Shin et al 2008). In any case, the flow evolution under a dynamically dominant magnetic field is out of the scope of this work.…”
Section: Physical Scenariomentioning
confidence: 99%